Frailty, MRI, and FDG-PET Measures in an Australian Memory Clinic Cohort - Jordan, Nan; Gvalda, Matthew; Cody, Ross; Galante, Olivia; Haywood, Cilla; Yates, Paul (Frontiers in Medicine, 2021)
Given that the global population is ageing, the number of age-related syndromes, such as frailty, is expected to rise in conjunction. Frailty is characterized by the loss of homeostatic reserve, rendering the individual vulnerable to poor health outcomes. Many biological mechanisms have been proposed to contribute to frailty. However, few studies have assessed the associations between frailty and brain diseases or neuroimaging biomarkers. Aims. The aims of this study were to measure the prevalence of frailty in a memory clinic; and to examine associations between frailty and brain changes found on magnetic resonance imaging (MRI) and 18-F Deoxyglucose (FDG) Positron Emission Tomography (PET) in memory clinic attendees. Methods. A 54-item Frailty Index was retrospectively assessed for all clinic attendees from 2014. Frailty was defined as FI>0.25. MRI were analyzed for stroke, Cerebral Small Vessel Disease (CSVD, including: cerebral microbleeds [CMBs], cortical superficial siderosis [CSS], white matter hyperintensity [WMH]) and neurodegenerative changes (MRI: mesial temporal atrophy (MTA), FDG PET regional hypometabolism), blind to clinical findings. Results. There were 209 clinic attendees in 2014, of whom 121 had MRI performed. The prevalence of frailty (using FI) in the memory clinic in 2014 was 38.3% overall, (patients without MRI: 43.2%, with MRI 34.7%, p=0.25). Frailty was associated with presence of deep WMH, increased severity of periventricular WMH and presence of CSS, but not neurodegeneration markers (MTA atrophy/FDG-PET hypometabolism). Conclusion. The findings support that previously-reported associations between frailty and imaging evidence of CSVD in other cohorts are also relevant to the Australian clinic setting. Given that a large proportion of memory clinic attendees are frail, there may be opportunities for interventions to reduce preventable adverse health outcomes such as falls and fractures, and reduce the prevalence and impact of frailty in this cohort.